1985
DOI: 10.1099/0022-1317-66-7-1601
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Herpes Simplex Virus Type 1 Penetration by Cytochalasins B and D

Abstract: SUMMARYInternalization of herpes simplex virus type 1 (HSV) KOS strain by HEp-2 cells was reversibly inhibited by pretreatment of cells with cytochalasins B and D. Internalization of virus following preincubation at 4 °C and temperature shift to 37 °C was normally preceded by a 5 to 8 min lag period and was complete within 20 to 30 min. A similar lag period followed HSV addition at 37 °C. Cytochalasin D was fivefold more active on HSV entry than cytochalasin B, with 50~ inhibition at 2 ~tM and 10 ~tM respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…Actin cytoskeleton has been shown to play a role in the infection of all the viruses tested in this study according to previous studies using the chemical actin inhibitor (Rosenthal et al, 1985;Kizhatil and Albritton, 1997;Bukrinskaya et al, 1998;Iyengar et al, 1998;Li et al, 1998;Locker et al, 2000). In addition, the Arp2/3 complex-mediated actin nucleation is sensitive to CC (Welch et al, 1998).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Actin cytoskeleton has been shown to play a role in the infection of all the viruses tested in this study according to previous studies using the chemical actin inhibitor (Rosenthal et al, 1985;Kizhatil and Albritton, 1997;Bukrinskaya et al, 1998;Iyengar et al, 1998;Li et al, 1998;Locker et al, 2000). In addition, the Arp2/3 complex-mediated actin nucleation is sensitive to CC (Welch et al, 1998).…”
Section: Discussionmentioning
confidence: 86%
“…Alternatively, cells infected with replication-competent viruses were lysed at time points before viruses entered the second replication cycle, except SIV, which required 48 h to give sufficient signal to be detected. Importantly, all the viruses tested in this study were reported to utilize actin cytoskeleton to infect cells as examined by using chemical inhibitors against actin such as cytochalasin (CC; Rosenthal et al, 1985;Kizhatil and Albritton, 1997;Bukrinskaya et al, 1998;Iyengar et al, 1998;Li et al, 1998). The infection efficiencies of viruses into cells expressing GFP were set at 100% throughout the study unless stated and the infection efficiencies into GFP-VCA-expressing cells relative to GFP-expressing cells were calculated.…”
Section: Gfp-vca Inhibits Infection Of Primate Lentivirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that endothelial cell structure is maintained by the cytoskeleton, which is possibly responsible for maintaining and restoring normal cell morphology and functions (21). The actin microfilaments, which are mainly composed of F-actin and actin-binding proteins, are a major component of the cytoskeleton and are intricately involved mechanically and biochemically in various cell processes, including cell division and motility (22). It is well established that the polymerization-depolymerization dynamics of actin is a crucial process in a wide variety of cellular functions (23).…”
Section: Discussionmentioning
confidence: 99%
“…The procedure used was essentially that of Rosenthal et al (1985). Confluent monolayers of RK cells in 24-well plates were incubated at 4 °C for 30 rain before use, infected with EHV-1 and incubated at 4 °C for 30 min to allow virus adsorption, but not penetration, to take place.…”
Section: Iodination Of Purified Virusmentioning
confidence: 99%